GUA BRAHOLO: KARAKTER HUNIAN MIKRO PADA AWAL KALA HOLOSEN DI GUNUNG SEWU - Handini, Retno; Widianto, Harry (BRIN, 1999)
Located in Semugih Village, Rongkop District, Gunung Kidul Regency, Yogyakarta Special Region Province, Braholo Cave is one of the prehistoric settlement caves located in the karst mountain range of Gunung Sewu. This cave was discovered by the Prehistoric Division of the National Archaeological Research Center, when a survey was carried out throughout the Mount Sewu area in 1996. Dozens of caves were found in the western part of this mountain and one of them is the Braholo Cave, which was then followed up by carrying out excavations in 1997 and 1998.